2023
DOI: 10.3390/ijpb14030055
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Physiological Traits and Phytochemical Compositions of Coffea canephora Beans from Lampung for Various Harvesting Stages and Soaking Durations

Yudithia Maxiselly,
Denisse Shafa Humaira,
Dwi Novanda Sari
et al.

Abstract: Coffea canephora, also known as Robusta, is one of the coffee species that dominates production in Indonesia. The morphology, physiology, and phytochemistry of Canephora coffee beans are affected by many factors, such as the fruit harvesting time and post-harvest processing. The maturity stage of coffee fruits at harvest time and post-harvest management will affect the various morpho-physiological and phytochemical compositions of the coffee beans. This research aimed to observe Canephora coffee beans’ morpho-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Based on studies, it has been observed that green Robusta coffee beans contain higher concentrations of caffeine and CGA, both of which exhibit bitterness and astringency taste in the coffee brew and are regarded as lower quality compared with green Arabica coffee beans (Bicho et al, 2011;Seninde & Chambers IV, 2020). Nonetheless, the phytochemical constituents of green Robusta coffee beans can be significantly influenced by various factors, including the agronomic environment and the methods used during post-harvest processing (Maxiselly et al, 2023). For instance, caffeine and CGA concentrations in green coffee beans negatively correlated with altitude (Girma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on studies, it has been observed that green Robusta coffee beans contain higher concentrations of caffeine and CGA, both of which exhibit bitterness and astringency taste in the coffee brew and are regarded as lower quality compared with green Arabica coffee beans (Bicho et al, 2011;Seninde & Chambers IV, 2020). Nonetheless, the phytochemical constituents of green Robusta coffee beans can be significantly influenced by various factors, including the agronomic environment and the methods used during post-harvest processing (Maxiselly et al, 2023). For instance, caffeine and CGA concentrations in green coffee beans negatively correlated with altitude (Girma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%